The Weakness of Cumulative Voting - Benaloh, Josh (2017)
Cumulative Voting is an electoral system in which each voter is allowed to cast multiple votes — some or all of which may be duplicate votes for a single candidate. It is sometimes used to elect members to a legislative body such as a parliament or city council, and its purpose is to achieve a more proportional representation than that which results from many other voting systems. Cumulative voting is most commonly used in municipal elections in the United States and Europe, but it has also been used for larger elections and is often used by corporations to elect their directors.